CCAFS Webinar on Gender and Social Inclusion (Sep 23, 2015) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
Sophia Huyer and Catherine Hill present an overview of the new CCAFS Gender and Social Inclusion (GSI) strategy.